Exploratory study on design principles and key technologies of Industry 4.0. (21st January 2022) - Kumar, Pramod; Bhadu, Jagdish; Singh, Dharmendra; Bhamu, Jaiprakash
The Fourth Industrial Revolution or Industry 4.0 mainly focused on digital transformation of manufacturing scenario that combines information and communication technologies to create quick responsive networking of systems for the organisation. Design principles and key technologies are collective terms and main pillars of Industry 4.0 which are significantly changing the manufacturing landscape from distant, esoteric concept to real and tangible. The current industries have to understand the design principles and advanced technologies with sustainability aspects for transforming their business towards the competitive environment. The manufacturers need to develop skills regarding these set of the design principles and technologies to align with current transformation. Therefore, this paper explores the design principles and key technologies with the discussion about sustainability aspects of these two main pillars of Industry 4.0. Articles from renowned journals and conferences were thoroughly studied and key points extracted to design the presented work. The authors elaborated concepts, emerging trends, applications and contributions of these building blocks in changing the current manufacturing scenario with the implications of interaction of design principles and key technologies in context of Industry 4.0. Major contributions of Industry 4.0 for sustainable manufacturing also elaborated at the end of the paper.